Efektivitas Pelatihan Mindfulness untuk Menurunkan Ego Depletion pada Mahasiswa Baru - Vonny Syafira; Ira Paramastri (Faculty of Psychology, Universitas Gadjah Mada, 2018)
This study aims to test the effectiveness of mindfulness-based interventions decrease ego depletion in new students. Hypothesis in this research is mindfulness-based intervention can decrease ego depletion of the new student. This study uses a quasi-experimental with the design of untreated-control-group with pretest-posttest using switching replication. This intervention consists of one session plus an opening session, planning and closing. A total of 15 new students with moderate to high ego depletion are divided into control and experiment groups. The instruments used in this study are EDS and KIMS. Quantitative analysis was performed by Mann-Whitney statistical test and qualitative analysis. The results showed that mindfulness-based interventions were significant to decreasing ego depletion in new students (U = 0.000, P <0.001) and the therapeutic effect of these interventions could persist at least two weeks post-intervention.